R-SYSTEM AND INFORMATION TECHNOLOGIES AS TOOLS FOR ECONOMIC INTELLIGENCE IN ORGANIZATIONS - A. Volchkov; N. Struzhkin (Вестник университета, 2017)
Evolution of contemporary information technologies, focus on market mechanisms for interaction between organizations, business activity in conditions of high uncertainty lead to necessity of implementation of various economic intelligence methods. One of such economic intelligence methods is the usage of R-system which allows to identify risks of business projects, analyze business partners and competitors using data from open data sources. Significant growth of computing power, evolution of intelligent data processing algorithms and development of simulation modeling allow to use R-system methods in the most efficient way.